Ultra-lightweight, super thermal-insulation and strong PP/CNT microcellular foams. (3rd May 2020) - Zhao, Jinchuan; Wang, Guilong; Wang, Chongda; Park, Chul B.
Abstract: The global energy crisis has been widely concerned by the public due to the massive energy requirement caused by rapid-developing economy and society. Ultra-lightweight, super-insulating, and strong polymer foams exhibit a promising prospect, in terms of saving materials and resources, and reducing energy consumption. However, there exists a great challenge to achieve highly expanded microcellular polymer with satisfactory thermal insulation performance. Herein, polypropylene (PP) with carbon nanotubes (CNTs) was used to prepare multifunctional foams by using batch foaming process with carbon dioxide. This cost-efficient and facile process endowed PP/CNT composite a variety of unprecedented advantages, including over 50-fold expansion ratio, a rather low thermal conductivity of 28.69 mW/m·K, and remarkably improved compressive strength. Acting as both crystal and cell nucleating agents, CNTs contributed to the fabrication of such ultralight foams with refined cell structure, which led to significantly reduced solid thermal conduction and enhanced mechanical properties. Moreover, thanks to CNTs' outstanding infrared radiation shielding capacity, the thermal radiation through the ultra-lightweight PP/CNT foam was significantly suppressed. Thus, ultra-lightweight, super thermal-insulation, and strong PP/CNT composite foams were achieved by using microcellular foaming technology, paving a way for designing and synthesizing multifunctional polymer-based composite foams for high-performance thermally insulating applications. Graphical abstract: Image 1